Effect of high-grain diet and residual frying oil on the quality of lamb meat (Research, Society and Development, 2020)
In addition to influencing performance, the use of new ingredients in the diet of production animals can influence meat quality. Were used 15 lambs, crossbred from Dorper x Santa Inês, divided into three experimental groups. Group 1 (Control) fed with Tifton hay and concentrate, in the proportion of 40:60; Group 2- animals fed a 100% high grain diet; Group 3- lambs fed with Tifton hay and concentrated with the inclusion of 6% residual frying oil. After 40 days of confinement, the animals were slaughtered and the Longissimus dorsi muscle was removed from the carcasses for analysis of meat quality attributes. There was no effect of the test diets (P > 0.05) on the physical parameters of the meat. The protein and lipid values were higher in the meat of the animals on the diet with residual oil. The moisture content of meat from animals on the high-grain diet showed higher values (P < 0.05) than that of other diets. This fact is attributed to the lower muscle development in animals on this diet, which may also have contributed to the levels of meat protein and lipids in this treatment. It was concluded that the diet with the inclusion of frying oil was the best among the test diets because it did not negatively impact the meat quality.